(untitled) (Comparative & International Education Series, 2021)
This chapter delineates what they really experience during study-abroad by focusing on one student of color’s English teaching experiences in Asia. This perceived absence, unfortunately, lead to the participant being treated as a non-ideal ELT instructor. The white students who participated in the same study-abroad, on the other hand, were all treated as ideal ELT instructors and received effective mentoring from and collaboration with the teachers at the host school. The chapter highlights the importance of discussions of frequently neglected topic in study-abroad: the effects of participants’ race, in particular, how their race affects how they access to and interact with the members of the host country, and how such access and interactions affect their learning experiences.